Economic viability of common bean variety BRS Estilo - da Silva, Osmira Fatima (2015)
This study aims to evaluate financially BRS Estilo, a variety of common bean (Phaseolus vulgaris L.), the carioca group, developed by â€œEmbrapa Rice and Beansâ€ and partners, estimating the regional economic benefit from the knowledge of the costs generation and transfer of technology and production system. The BRS Estilo variety was evaluated in four successive seasons: 2010/2011, 2011/2012, 2012/2013 and 2013/2014. The BRS Estilo technology contribution to the bean agribusiness in Brazil was R$ 239.431.760,83, about US$ 106 million during the period. The transfer process of the BRS Estilo to the productive sector represents 7,5% of the total cost on developing technology, which began in 2000. In addition to the economic benefit provided by the adoption of this technology, there has also been generating more jobs in its supply chain and also increasing the product offered in the market.JEL-Code | O13; Q16; R32.